Outcome of Corticosteroid Injection in Reducing the Intensity of Pain in Patients with Plantar Fasciitis - Waqas Ali, Arif Kaleem, Aqeel Moazzam, Zohaib Nadeem, Nisar Ahmad, Imran Ahmad, Abdul Aziz, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Plantar fasciitis is one of the most common causes of heel pain, accounting for about one million patient visits per year in the United States. Objectives: The main objective of the study is to find the outcome of corticosteroid injection in reducing the intensity of pain in patients with plantar fasciitis. Material and methods: This descriptive study was conducted in CMH Kharian during March 2022 to September 2022. Data was collected with the permission of ethical committee of hospital. All the data related to physical examination, BMI, age, history of diseases and socioeconomic status were collected. The injections were applied to all patients who included unilateral foot symptoms and didn't respond to conservative treatment for at least six months. Results: Data was collected from 100 patients. Most of the cases were males 63 (63.3%) and rest 36 (36.7%) were females. Age with mean standard deviation was 38.15±10.26 years and had body mass index 23.11±13.51 kg/m2. Practical implication: This study will help us to treat the plantar fasciitis treated with single injection of corticosteroid injection resulted in significant pain reduction. Conclusion: It is concluded that plantar fasciitis treated with single injection of corticosteroid injection resulted in significant pain reduction in our patients. We recommend steroid injection in patients who are refractory to 6 weeks anti-inflammatory drugs and physiotherapy treatment. Keywords: Pain, Reduction, Injection, Corticosteroid, Significant, Treated